Dye-sensitized solar cell goes solid - Zhang, Qichun (2013)
Conventional dye-sensitized solar cells could potentially replace high-cost silicon-based solar cells, but the liquid electrolyte makes manufacture challenging. CsSnI3-based dye cells, constructed in solid-state form, pose a compelling solution.